A Conversation with Cornelius Holtorf - Pintucci, Alessandro (Ex Novo: Journal of Archaeology, 2021)
Cornelius Holtorf is UNESCO Chair on Heritage Futures at Linnaeus University. He reads prehistoric archaeology, social anthropology and physical anthropology in Germany, England and Wales. In 1998 he gained his PhD and was subsequently employed in research and teaching at the University of Gothenburg (1998-1999), the University of Cambridge (1999-2002), the Swedish National Heritage Board in Stockholm (2002-2004) and the University of Lund (2005-2008). Since 2008 Cornelius have been working at Kalmar where he is currently a Professor of Archaeology at Linnaeus University and Director of the Graduate School in Contract Archaeology (GRASCA).